Airway microbiota across age and disease spectrum in cystic fibrosis. Issue 5 (16th November 2017) - Zemanick, Edith T.; Wagner, Brandie D.; Robertson, Charles E.; Ahrens, Richard C.; Chmiel, James F.; Clancy, John P.; Gibson, Ronald L.; Harris, William T.; Kurland, Geoffrey; Laguna, Theresa A.; McColley, Susanna A.; McCoy, Karen; et al.
Our objectives were to characterise the microbiota in cystic fibrosis (CF) bronchoalveolar lavage fluid (BALF), and determine its relationship to inflammation and disease status. BALF from paediatric and adult CF patients and paediatric disease controls undergoing clinically indicated bronchoscopy was analysed for total bacterial load and for microbiota by 16S rDNA sequencing. We examined 191 BALF samples (146 CF and 45 disease controls) from 13 CF centres. In CF patients aged <2 years, nontraditional taxa ( e.g . Streptococcus, Prevotella and Veillonella ) constituted ∼50% of the microbiota, whereas in CF patients aged ≥6 years, traditional CF taxa ( e.g . Pseudomonas, Staphylococcus and Stenotrophomonas ) predominated. Sequencing detected a dominant taxon not traditionally associated with CF ( e.g . Streptococcus or Prevotella ) in 20% of CF BALF and identified bacteria in 24% of culture-negative BALF. Microbial diversity and relative abundance of Streptococcus, Prevotella and Veillonella were inversely associated with airway inflammation. Microbiota communities were distinct in CF compared with disease controls, but did not differ based on pulmonary exacerbation status in CF. The CF microbiota detected in BALF differs with age. In CF patients aged <2 years, Streptococcus predominates, whereas classic CF pathogens predominate in most older children and adults. Bacterial taxa detected in cystic fibrosis bronchoalveolar lavage fluid differ by age and inflammatory response http://ow.ly/2uV230eFA0W